Mirroring Nature? Men's and Women's Models of Conception in Telefolmin - Jorgensen, Dan (The Australian journal of anthropology, 1983)
Telefol men are reluctant to talk about conception, which they claim is ‘bad talk’. Despite this, they espouse a theory of conception, and this theory accords well with the general form of Telefol kinship. Telefol women are cognizant of the men's model, but have a further one of their own which differs from that of the men in regard to the respective contributions of the sexes and the domains in which these contributions are relevant. These domains may be glossed as kinship and cult, and this paper argues that it is the relation between these domains, as well as between women and men, that is the bone of contention.